Features of the administrative and legal mechanism for regulating the security environment in the state - Steblovskyi , Vyacheslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article analyzes the features of the administrative and legal mechanism for regulating the security environment in Ukraine. The relevance of the research problem is emphasized in the context of modern challenges to Ukraine's national security, particularly under martial law conditions.The aim of the article is to clarify the essence of the administrative and legal mechanism for regulating the security environment in the state and its components.Scientific approaches to understanding the concepts of «security environment» and «administrative and legal regulation» in the field of national security are analyzed. It is determined that national security is the state's ability to withstand external and internal negative factors that can lead to economic and political destabilization in the country. The main goal of the administrative and legal mechanism for regulating the security environment is to create and maintain a stable, adaptive system for protecting national interests under martial law conditions. Based on the analysis of current legislation and scientific literature, the structure of the administrative and legal mechanism for regulating the security environment is defined, which includes regulatory, institutional, functional, information-analytical, resource, control-supervisory, and international partnership components. The legal framework regulating the sphere of national security of Ukraine is characterized. Particular attention is paid to ensuring a balance between necessary restrictions under martial law and preserving democratic principles and human rights protection. It is emphasized that special attention should be paid to the development of early warning systems about potential threats, which allows for the most prompt response to changes in the security environment. The importance of international cooperation in the context of Ukraine’s Euro-Atlantic integration is underlined. Prospects for further research in this area are identified.